The Influence of Word of Mouth and Digital Marketing on Kopi Cuss Marketing Strategy - Iriandy, Iriandi; Bahar, Ayu Saputri; Purnamasari, Fitry; Niza, Andi Khaerun; Aliah, Nurul (PINISI Discretion Review, 2025)
This study aims to analyze the influence of Word of Mouth (WOM) and Digital Marketing on marketing strategies in the mobile coffee business "Kopi Cuss". The study was conducted with a quantitative descriptive approach using a questionnaire distributed to 106 respondents, who were active consumers of Kopi Cuss in the last six months. The results of the linear regression test showed that WOM had a significant influence on marketing strategies, while digital marketing did not have a significant influence partially. However, the results of the simultaneous test showed that both had a significant influence together. These findings indicate the importance of synergy between informal communication from consumers and digital marketing strategies in building brand awareness and customer loyalty, especially among the younger generation.